A critical review on application of photocatalysis for toxicity reduction of real wastewaters - Rueda-Marquez, Juan José; Levchuk, Irina; Fernández Ibañez, Pilar; Sillanpää, Mika (Journal of cleaner production, 2020)
Advanced oxidation processes (AOPs) such as photocatalysis are widely studied for degradation of organic pollutants of contaminants of emerging concern (CECs). However, degradation of organic pollutants leads to formation of by-products, which may be more toxic than parental contaminants. The toxicity of wastewater treated by photocatalysis is topical issue. In this review paper recent studies concerned with photocatalytic detoxification of real industrial and municipal wastewater were assembled and critically discussed. Such issues as challenges for application of photocatalytic wastewater detoxification, feasibility of various toxicity tests, reuse of photocatalysts, cost estimation, etc. were considered. Based on reviewed literature it can be suggested that photocatalysis might not always be a promising treatment method for degradation of organic pollutants in real wastewaters and/or wastewater detoxification from the application point of view. [Display omitted] •The effect of different toxicity assays after and during photocatalysis is discussed.•The most used standard toxicity might not be feasible for urban wastewater.•Currently photocatalysis might not be viable for real application.